Planning Working Drawings of Irrigation Channels in Lampeantani Village - Sianto, La (Lembaga Riset dan Inovasi Masyarakat Madani, 2023)
In Indonesia there are several regions that have great potential in the agricultural sector, one of which is Lampeantani Village, Rarowatu District, Bombana Regency. The local government is well aware of the potential possessed by the region so it is very supportive of activities related to the agricultural sector, because the number of problem areas is large, the handling needs to be done on a priority scale. One way is to provide a picture of a work plan to repair the existing canals in Lampeantani Village. The implementation of Community Service activities, namely the working drawings of the irrigation canal, is running very well and smoothly according to the previous activity plan. This activity began with outreach with the Village Government, then continued with site visits and field measurements. The result of this community service is a drawing of an irrigation canal plan. Based on the results of the implementation of this PKM, it is hoped that the Lampeantani Village Government can immediately carry out work based on the existing drawings.